Pretilachlor Releasable Polyurea Microcapsules Suspension Optimization and Its Paddy Field Weeding Investigation - Chen, Hongjun; Liu, Xiu; Deng, Shuqi; Wang, Hongkun; Ou, Xiaoming; Huang, Linya; Li, Jingbo; Jin, Chenzhong (Frontiers in Chemistry, 2020)
In this study, pretilachlor was encapsulated into polyurea microcapsules prepared by water-initiated polymerization of polyaryl polymethylene isocyanate and eventually made into pretilachlor microcapsules suspension (PMS). We used response surface methodology (RSM) combined with the Box–Behnken design (BBD) model to optimize the formulation of PMS. The encapsulation efficiency (EE) of PMS was investigated with respect to three independent variables including wall material dosage (X1), emulsifier dosage (X2), and polymerization stirring speed (X3). The results showed that the regression equation model had a satisfactory accuracy in predicting the EE of PMS. To achieve an optimal condition for PMS preparation, the dose of wall material was set to 5%, the dose of emulsifier was set to 3.5% and the polymerization stirring speed was set to 200 rpm. The EE of PMS was up to 95.68% under the optimized condition, and the spherical shape with smooth surface morphology was observed. PMS was also proven to have delayed release capability and in vivo herbicidal activity against barnyard grass [Echinochloa crusgalli (L.) Beauv.] with an LC50 value of 274 mg/L. Furthermore, PMS had efficient weed management compared to commercially available 30% pretilachlor emulsifier (PE), showing a promising potential application for weeding paddy fields.